2014
DOI: 10.1039/c4nr00534a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and recyclable triple-shelled Ag@Fe3O4@SiO2@TiO2 photocatalysts for degradation of organic pollutants and reduction of hexavalent chromium ions

Abstract: Herein, we demonstrate the design and fabrication of the well-defined triple-shelled Ag@Fe3O4@SiO2@TiO2 nanospheres with burr-shaped hierarchical structures, in which the multiple distinct functional components are integrated wonderfully into a single nanostructure. In comparison with commercial TiO2 (P25), pure TiO2 microspheres, Fe3O4@SiO2@TiO2 and annealed Ag@Fe3O4@SiO2@TiO2 nanocomposites, the as-obtained amorphous triple-shelled Ag@Fe3O4@SiO2@TiO2 hierarchical nanospheres exhibit a markedly enhanced visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(58 citation statements)
references
References 59 publications
1
49
0
1
Order By: Relevance
“…The experimental results indicated that the shortening of the duration of the heat treatment not only significantly lowers the extent of the interaction between Fe 3 O 4 core and TiO 2 coatings but also limits the extent of the oxidation of the Fe 3 O 4 core. Therefore, several groups worked on improving the photocatalytic activity of magnetic photocatalysts by depositing TiO 2 /Fe 3 O 4 hybrids with silver, platinum, or nitrogen (Xu et al 2005, Su et al 2014b. Some studies also introduced SiO 2 as an inert substance between TiO 2 procedure via charge separation.…”
Section: Tio 2 /Sno Hybrid Photocatalytic Systemmentioning
confidence: 98%
“…The experimental results indicated that the shortening of the duration of the heat treatment not only significantly lowers the extent of the interaction between Fe 3 O 4 core and TiO 2 coatings but also limits the extent of the oxidation of the Fe 3 O 4 core. Therefore, several groups worked on improving the photocatalytic activity of magnetic photocatalysts by depositing TiO 2 /Fe 3 O 4 hybrids with silver, platinum, or nitrogen (Xu et al 2005, Su et al 2014b. Some studies also introduced SiO 2 as an inert substance between TiO 2 procedure via charge separation.…”
Section: Tio 2 /Sno Hybrid Photocatalytic Systemmentioning
confidence: 98%
“…[1][2] The interactions between the core and shell material can drastically improve the overall performance of the core/shell nanostructure system and even create advantageous synergetic effects, which may bring a series of opportunities for their potential applications such as chemical sensors, light-emitting diodes, photocatalysis. [6][7][8] This simple method to fabricate hierarchical core/shell nanoarchitecture is highly desirable now as well as in the near future for energy and environment cleaning applications. It can efficiently generate charge separation and the large aspect ratio can increase the active sites and wide range of light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…28 In the same way, the direct interaction of chemically reactive Ag with TiO 2 may oxidize Ag into AgO at the TiO 2 -Ag junction. In order to avoid these problems, the iron oxide and Ag cores were coated by the non-toxic and hydrophilic inorganic or organic materials including SiO 2 …”
Section: 26mentioning
confidence: 99%
“…6). Aer subtracting MB removal in the dark, the reaction rate constant values of PAM, PAM-TiO 2 NC and porous TiO 2 Table S-1 †) 28 because of their comparatively greater affinity for water and MB, higher probability to directly contact MB, hierarchical porosity, higher surface area, narrower bandgap (see Fig. S-1 †), and orderly crystalline anatase phase (known to be more photoactive).…”
Section: Degradation Of Mbmentioning
confidence: 99%